Guided by the Agrobiodiversity Index, nearly half of 350 keystone food and agricultural companies provide evidence that they are contributing towards improving soil health and increasing agrobiodiversity - CGIAR Research Program on Water, Land and Ecosystems (2021)
The Agrobiodiversity Index was used to guide the Soil and Agrobiodiversity component of the Food and Agriculture Benchmark of the World Benchmarking Alliance (WBA) and to encourage food and agriculture companies to provide evidence that they are contributing towards improving soil health and agrobiodiversity. WBA applied this benchmark with 350 keystone food and agricultural companies; 45% of them provided adequate evidence to demonstrate that they are contributing to improving soil health and agrobiodiversity.